Bankers’ perception on the roles of whistleblowing: Demographic evidence from Malaysia / Nurmazilah Dato’ Mahzan, Mohamad Afzhan Khan Mohamad Khalil and Anuar Nawawi - Mahzan (Dato’), Nurmazilah; Mohamad Khalil, Mohamad Afzhan Khan; Nawawi, Anuar (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
The purpose of this study is to develop a reliable and valid construct for roles of whistleblowing and to assess the association between respondents’ demographic characteristics and their perception on whistleblowing. The fraud triangle and deontology theories underpin the development of the survey instrument. Survey questionnaires were administered to 553 respondents in the Malaysian financial sector using face to face data collection procedure. A total of 334 questionnaires were usable for the final analysis. Cochran’s method was adopted for sample size determination. The data collected were cleaned and issues on reliability, validity and normality of distribution were resolved. The confirmatory factor analysis (chi square = 4.15; GFI = 0.90; CFI= 0.91; NFI = 0.89; TLI = 0.89; RMSEA = 0.10), normality (skewness < 1.50) and reliability (Cronbach alpha = 0.90; composite reliability = 0.92; average variance extracted = 0.54) results were convincing. Subsequently, a one way ANOVA was employed to test for significant associations between the respondents’ demographic characteristics and their perception on the roles of whistleblowing. It was found that respondents’ age (p = 0.01), position (p = 0.01) and working experience (p = 0.03) had significant bearings on their perception of the roles of whistleblowing within the Malaysian financial sector.